Insects of forensic importance associated to cadaveric decomposition in a rural area of the Andean Amazon, Caquetá, Colombia (2018)
ABSTRACT: Forensic entomology is a frequently used tool to estimate the time interval between death and the discovery of the corpse. Succession of arthropods associated with cadaveric decomposition was monitored in a rural area of the Municipality of Florencia, Department of Caquetá, Colombia. Three pigs (Sus scrofa) were used as study models. Insect sampling, and monitoring of carcasses and environmental conditions were carried out every five hours. The total time from death to skeletonization was of 545 hours (22.7 days). A total of 30833 insect individuals were collected. Specimens were distributed in nine orders, 46 families, 95 genera and 106 species. Diptera was the most abundant, with 23215 individuals (75.3%), followed by Coleoptera, with 3711 individuals (12%), and Hymenoptera, with 3154 individuals (10.2%). Immature stages of Cochliomyia macellaria, Chrysomya albiceps, Hemilucilia semidiaphana and Ophyra aenescens were the main species involved in tissue consumption and acceleration of the decomposition process. Due to the presence of ants Cheliomyrmex sp., Camponotus sp. and Dinoponera sp., and coleopterans Hister sp., Acylophorus sp. and Philonthus spp., it was not possible to obtain sufficient Diptera egg masses for rearing the colonizing species. These results can be used as a standard to determine the postmortem interval in criminal investigations in the rural area of the Andean Amazon, Caquetá, Colombia.